PHYSICAL AND CHEMICAL PROPERTIES OF ARUK CASSAVA RICE - Budi Santoso; Carles Carles; Parwiyanti Parwiyanti; Rindit Pambayun (BPFP Faperta UNIB, 2012)
The objective of the research is to determine the effect of peeling methods and different periods of immersion on physical and chemical characteristics of aruk rice cassava. The research used Factorial Block Randomized Design with two factor treatments and three replications. A factor was the method of peeling (tubers washed with skin and peeled, tubers peeled and washed, and tubers peeled, washed and scraped the mucus layer) and the B was the long immersion (3 days, 5 days, and 7 days). The parameters observed were included yield, color, texture, water content, protein content and levels of cyanide. The results showed that the method of peeling had significant affect the yield, lightness, crude fiber content, and water content. The long immersion treatirent had significant influenced the yield, chroma, crude fiber content, and water content. Interaction farktor A and B have significant real impact on yield, lightness, hue and crude fiber content. Treatment A2B3 (Tubers peeled and washed, and 7 days immersion) is the best trearment is obtained with characteristics yield 17%, lightness 77.63%, chroma 14.13%, hue 82.47 . texture 28.53 gf, the crude fiber content 6.19%, and water content 11 .28%.